2020
DOI: 10.2503/hortj.utd-147
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Carotenoid Accumulation and Carotenogenic Gene Expression During Fruit Ripening in Red Colored Pulp of ‘Siam Red Ruby’ Pumelo (<i>Citrus grandis</i>) Cultivated in Thailand

Abstract: The 'Siam Red Ruby' (Citrus grandis) is a new lycopene-accumulating pumelo variety, which is grown only in the Pakpanang area of the Nakhon Si Thammarat province of Thailand. In this study, we harvested 'Siam Red Ruby' fruit at five ripening stages, and the changes in the accumulation of carotenoid and carotenogenic gene expression were investigated in the pulp. During the ripening process, the contents of phytoene, ζ-Carotene, lycopene, β-carotene, β-cryptoxanthin, and all-trans-violaxanthin increased gradual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Some studies proposed that low transcript level of β-LCY2 gene or mutations in amino acids critical for the β-LCY2 activity as the molecular mechanisms of lycopene accumulation in Red Anliu orange ( Lu et al., 2016 ) and red grapefruits ( Alquézar et al., 2009 ; Alquézar et al., 2013 ). Similarly, a reduction in LCYs gene expression was proposed in pink lemon and red pummelos ( Lana et al., 2020 ; Promkaew et al., 2020 ; Tatmala et al., 2020 ). Nonetheless, neither key differences in the expression of β-LCYs nor mutations in their sequences were associated with lycopene accumulation in Cara Cara ( Alquézar et al., 2008 ; Lu et al., 2017 ).…”
Section: Discussionmentioning
confidence: 66%
“…Some studies proposed that low transcript level of β-LCY2 gene or mutations in amino acids critical for the β-LCY2 activity as the molecular mechanisms of lycopene accumulation in Red Anliu orange ( Lu et al., 2016 ) and red grapefruits ( Alquézar et al., 2009 ; Alquézar et al., 2013 ). Similarly, a reduction in LCYs gene expression was proposed in pink lemon and red pummelos ( Lana et al., 2020 ; Promkaew et al., 2020 ; Tatmala et al., 2020 ). Nonetheless, neither key differences in the expression of β-LCYs nor mutations in their sequences were associated with lycopene accumulation in Cara Cara ( Alquézar et al., 2008 ; Lu et al., 2017 ).…”
Section: Discussionmentioning
confidence: 66%
“…Similar results were reported in ‘Siam Red Ruby’, a new lycopene-accumulating pummelo variety in Thailand. Gene expression results showed that increases in the expression of upstream genes (CitPSY, CitPDS, CitZDS, CitZISO, and CitCRTISO) and decreases in the expression of downstream genes (CitLCYb1, CitLCYb2, CitLCYe, CitHYb and CitHYe) were the main mechanisms controlling lycopene accumulation in the pulp of ‘Siam Red Ruby’ [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another less explored model of carotenoid synthesis occurs in non-climacteric citrus fruits. These fruits belong to different species of the Citrus genus, which shows a wide range of colorations in its peel and pulp due to the different proportions and composition of carotenoids [ 129 , 130 , 131 , 132 ]. In these fruits, light quality affects dramatically the degreening and carotenoid accumulation in the fruit pericarp.…”
Section: Carotenoid Synthesis In Plantsmentioning
confidence: 99%